ANALISIS KARAKTERISTIK GAYA BELAJAR MAHASISWA PGSD UM PALANGKARAYA - Zannah, Fathul; Sari Dewi, Indah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
Learning style is a learning characteristic that is closely related to a person's way of absorbing knowledge. Information related to the characteristics of learning styles is very useful for lecturers to improve the quality of learning. The purpose of this study was to analyze the characteristics of learning styles (auditory, visual and kinesthetic) students of the Elementary School Teacher Education University of Muhammadiyah Palangkaraya by using descriptive qualitative research methods. The subjects in this study were 55 fourth semester students who took the Basic Concept Science course. The results showed that students had learning styles that varied between auditory, visual and kinesthetic learning styles but with the frequency of learning style tendencies that were more dominant in the kinesthetic learning style (75.1%). These findings can be one of the references for lecturers in the course to adjust their lecture activities with the characteristics of their students.